An application of survival analysis on the determinants of employmentlongevity in Namibia: Evidence from 2018 Labour Force Survey - Oyedele, Opeoluwa; Angula, Liina E.M.; Mutorwa, Klemens T. (Namibian Journal for Research, Science and Technology, 2022)
Employment longevity shapes the total work experience of an employee’s career, in addition to providing additional information about the employment stability of the employee and employer. However, in recent years, employment stability has decreased globally, with Namibia being amongst the highly affected countries where workers are having a high number of short-term employment records over the course of their careers. In this paper, the Kaplan-Meier and Cox Proportional Hazard techniques were used to estimate the survival of employment longevity for employed adults in Namibia using the 2018 Namibia Labour Force Survey. Results showed that majority of the employees were working in the private enterprises and government institutions, attained junior and senior secondary education, never married, worked for a paying job and were from the Khomas, Erongo and Otjozondjupa regions. Likewise, majority of the employees employed for less than 1 year and for 1-2 years were aged 20-29 years, while majority employed for 3-5 years and 6-10 years were aged 30-39 years. The employed adults’ characteristics such as age group, type of employer, highest education attained, marital status, region, current schooling status and sex had a significant association with their survival of employment longevity. In addition, employees aged 30-39 and 40-49 years, employed in non-profit institutions, parastatals and government institutions, and from the Oshikoto, Omaheke, Oshana, Khomas, Erongo and Otjozondjupa regions had a high survival of employment longevity, while employees employed in privately owned informal enterprises and had already attained a technical or vocational certificates/diplomas, junior and senior secondary education had a low survival. It is therefore recommended that all relevant organizations and governmental ministries that deals with employment and labour matters should frequently engage all employers through their respective human resources departments, to further assist in the creation and implementation of favourable employment contracts that best suits their respective employees, especially, for those employed in privately owned informal enterprises, employed for less than 1 year, 1-2 years and 3-5 years, who are in their 20s and 30s (age-wise), and already attained a technical or vocational certificates/diplomas, junior and senior secondary education